Global ocean governance in the Anthropocene: From extractive imaginaries to planetary boundaries?. Issue 5 (5th December 2022) - Stephens, Tim
Abstract: As with other fields of international law addressing human‐nature relations, the Anthropocene invites the reappraisal and reimagining of the law of the sea, the primary normative framework through which states regulate access to, and the use of, the global ocean. The UN Convention on the Law of the Sea (UNCLOS) effected a major shift in global ocean governance towards a public order of the seas. However, the law of the sea remains substantially tethered to a Holocene conception of the ocean as a stable environmental domain of extractive exploitation and jurisdictional demarcation. This is illustrated by the confined scope of negotiations on a new implementing agreement under UNCLOS on the conservation and use of marine biodiversity beyond national jurisdiction. Additionally, there has been limited acknowledgment of the multiple sites at which ocean governance in the Anthropocene takes place, in particular the central role of the UN Framework Convention on Climate Change (UNFCCC) and the Paris Agreement on Climate Change. It is contended that one way forward for addressing both these conceptual constraints and the UNCLOS and UNFCCC regime coordination challenges is the adoption of global ocean governance goals informed by the 'Planetary Boundaries' framework.